Thioesterification and Selenoesterification of Amides via Selective N–C Cleavage at Room Temperature: N–C(O) to S/Se–C(O) Interconversion - Rahman, Md. Mahbubur; Li, Guangchen; Szostak, Michal (Synthesis, 2020)
The direct nucleophilic addition to amides represents an attractive methodology in organic synthesis that tackles amidic resonance by ground-state destabilization. This approach has been recently accomplished with carbon, nitrogen and oxygen nucleophiles. Herein, we report an exceedingly mild method for the direct thioesterification and selenoesterification of amides by selective N–C(O) bond cleavage in the absence of transition metals. Acyclic amides undergo N–C(O) to S/Se–C(O) interconversion to give the corresponding thioesters and selenoesters in excellent yields at room temperature via a tetrahedral intermediate pathway (cf. an acyl metal).
Keywords: amides; N–C activation; metal-free; thioesters; selenoesters; thioesterification; selenoesterification; tetrahedral intermediates